Pengaruh Tingkat Pendidikan dan Pemahaman Keagamaan terhadap Tingkat Pengamalan Keagamaan Masyarakat Di Desa Nusuk Kabupaten Kaur - Noni Witisma (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: The Effect of Education Level and Religious Understanding on the Level of Community Religious Practices in Nusuk Village, Kaur Regency. The purpose of this study was to determine the effect of education level on community religious practice in Nusuk Village, Kaur Regency; To determine the effect of religious understanding on community religious practice in Nusuk Village, Kaur Regency; To find out the influence between the level of education and religious understanding on the level of community religious practice in Nusuk Village, Kaur Regency. This type of research is classified as field research with a quantitative approach. Data collection techniques used were observation, questionnaires and documentation. Based on the results of the study, it is known that there is a significant influence between the level of education with community religious practice in Nusuk Village, Kaur Regency. This is evidenced from the results of the analysis obtained that the t-count> from the t-table, namely t-count of 4.362 while the t-table of 2,000.There is a significant influence between religious understanding with community religious practice in Nusuk Village Kaur Regency. This is evidenced from the analysis results obtained t-count> t-table, namely t-count of 5.583 and t-table of 2,000.There is a significant influence between the level of education and religious understanding of the level of religious practice of the community in Nusuk Village Kaur District. This is evidenced from the results of the analysis obtained by F-count of 42.937 with f-table of 3.11. This means that F-count> f-table (42.937> 3.11). Keywords: Level of education, religious understanding, and religious practice.